Planeación de la producción en un sistema de producción Seru, considerando heterogeneidad para balancear tiempos de producción y minimizar el consumo de energía (2020)
With the rise of Industry 4.0 an era of real-time global connectivity between customers and the processes that transform consumer goods is imminent. Faced with the need to satisfy the current dynamic demand, the Japanese technology industry has developed an innovative production system called Seru, which is distinguished by its satisfactory results in economic and environmental terms. This study poses a production planning problem in a Seru production system considering heterogeneous workers and the energy consumption of production. To solve it, a multi-objective mathematical model is proposed to balance the production time between workers (intra-Seru) and between serus (inter-Seru) and minimize the total energy consumption. For larger instances, a metaheuristic algorithm is developed based on the evolutionary algorithm NSGA-II. Finally, the effectiveness of the proposed genetic algorithm is determined through a series of metrics that evaluate the convergence and variability of the frontier that it generates.